The heir eaudiobook - Cass, Kiera (The Selection, 2015)
A new era dawns in the world of Kiera Cass's #1 New York Times bestselling Selection series America and Maxon's fairy-tale romance enchanted readers from the very first page of The Selection. Now find out what happens after happily ever after in this fourth captivating novel, perfect for fans of Veronica Roth's Divergent, Lauren Oliver's Delirium, or Renée Ahdieh's The Wrath & the Dawn. Twenty years ago, America Singer entered the Selection and won Prince Maxon's heart. Now the time has come for Princess Eadlyn to hold a Selection of her own. Eadlyn doesn't expect anything like her parents' fairy-tale love story...but as the competition begins, she may discover that finding her own happily ever after isn't as impossible as she's always thought. A new generation of swoon-worthy characters and captivating romance awaits in the fourth book of the Selection series! Don't miss The Betrothed, a glittering royal romance sure to captivate Kiera Cass's legion of loyal readers and lovers of courtly intrigue alike!